Together In Lesema: Living Islamic Law among Customary Dani Muslims Polygamy Practice in Papua - Yamin, Ade; Wijayati, Mufliha; Makatita, Ahmad Syarif; Marwan Sileuw (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
The practice of polygamy (nage apik) within the Dani Muslim Community in Walesi Village of Jayawijaya Papua exhibits distinctive and unique characteristics. This article aims to reveal the practice among the Dani Muslims who apparently place their wives in the same house (called lesema). A qualitative approach using Spreadley’s ethnographic method serves as the primary data collection tool through observation and in-depth interviews with the informants. A review of relevant literature is conducted to contextualize the article within the existing literature. The data are analyzed interpretively by considering the ethical and emic principles. This article finds that first, polygamy for Muslim Dani is not only a way for continuing the descendants but also for asserting authority over the territory and taking responsibility for maintaining the community’s continuity. Second, living harmoniously in lesema is a practice aimed at preserving communal unity without barriers while also serving as a space for transferring knowledge on how to be a Dani woman. Third, polygamy within the Muslim Dani is seen as an extension of their cultural practices, accepted as a necessity and a solution to social issues within the community. The practice furthermore provides a new perspective on understanding the characteristics of Indonesian society regarding the role of women in households. It also illustrates how Islamic law intertwines with local traditions based on the history, level of understanding, natural characteristics, and lifestyle of its community.